1988
DOI: 10.1007/bf01874796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet and feeding time on daily variations in plasma insulin, hepatic c-AMP and other metabolites in a teleost fish,Dicentrarchus labrax L.

Abstract: Juvenile sea bass, 1.5 years old, of mixed sex, held on long photoperiods were fed early on the photoperiod and late on the photoperiod, using different diets. Fish fed natural diets showed a daily rhythmicity of plasma insulin, liver c-AMP, plasma glucose, liver glycogen and muscle glycogen content, however, fish fed a commercial diet did not show this daily rhythmicity except for plasma insulin levels. In addition, these fish had significantly lower levels of plasma insulin, liver c-AMP and plasma glycerol t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 24 publications
1
17
1
1
Order By: Relevance
“…Most information concerning changes in blood insulin concentrations in fish suggests that hormone changes are directly related to feeding times and the nature of the diet (e.g., Perez et al 1988, Sundby et al 1991). An example of this relationship is to be found in a recent study of Dicentrarchus labrux (Perez et al 1988) in which the peak plasma insulin levels were found in the second half of the photophase when the food provided was their natural prey species (Boops hoops); the pattern was reversed when the animals were fed artificial diets.…”
Section: Die1 Rhythm Of Feedingmentioning
confidence: 99%
“…Most information concerning changes in blood insulin concentrations in fish suggests that hormone changes are directly related to feeding times and the nature of the diet (e.g., Perez et al 1988, Sundby et al 1991). An example of this relationship is to be found in a recent study of Dicentrarchus labrux (Perez et al 1988) in which the peak plasma insulin levels were found in the second half of the photophase when the food provided was their natural prey species (Boops hoops); the pattern was reversed when the animals were fed artificial diets.…”
Section: Die1 Rhythm Of Feedingmentioning
confidence: 99%
“…The relative importance of the feeding time and of the light/ dark alternation, as synchronizer of metabolic or endocrine parameters have been studied by several authors (Higgs and Eales 1977;Spieler et al 1978;Bry 1982;Perez et al 1988). However, in most of these studies, food was presented to the fish at times that did not necessarily coincide with their natural feeding rhythm (if indeed we can admit that such a rhythm is present in teleosts in general).…”
Section: Introductionmentioning
confidence: 97%
“…The time of feeding has been shown to be of prime importance in the synchronization of such rhythms Laidley and Leatherland 1988;Perez et al 1988;Sundby et al 1991). However, in most of these studies, the fish were fed during the normal workday period, receiving only one meal per day, or even less.…”
Section: Introductionmentioning
confidence: 99%